The House of Saulx-Tavanes Versailles and Burgundy, 1700-1830 - Forster, Robert (Johns Hopkins University Press, 2019)
Originally published in 1971. In The House of Saulx-Tavanes: Versailles and Burgundy, 1700-1830, Professor Robert Forster examines the noble family of Saulx-Tavanes from the reign of Louis XIV to the Restoration. He provides readers with an account of a single aristocratic family's relationship to the changing political culture of the eighteenth century. Forster explores how an old aristocratic family promoted itself in the royal court, how the Saulx-Tavanes managed their estate remotely from Paris, and how the family's relationship to its creditors changed over time. Forster examines the ambiguities of one noble family's transition from provincial independence to courtly dependence and, eventually, to revolution. This book is an account of how the Saulx-Tavanes-a family of émigré nobles-preserved their life, revenue, reputation, esteem, and place in a French society transformed by political change and revolution.